2013
DOI: 10.1007/s10461-013-0593-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Structural-Level Needle/Syringe Programs to Reduce HCV and HIV Infection Among People Who Inject Drugs: A Systematic Review

Abstract: Needle-syringe programs (NSP) have been effective in reducing HIV and hepatitis C (HCV) infection among people who inject drugs (PWID). Achieving sustainable reductions in these blood-borne infections requires addressing structural factors so PWID can legally access NSP services. Systematic literature searches collected information on NSP coverage and changes in HIV or HCV infection prevalence or incidence at the population level. Included studies had to document biomarkers (HIV or HCV) coupled with structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(112 citation statements)
references
References 38 publications
4
108
0
Order By: Relevance
“…Available data have shown intervention measures in PWIDs can reduce both prevalence and incidence of HCV infection [2,3,17]. These actions have focussed around injecting drugs as this was, and still remains the dominant route for HCV transmission in England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data have shown intervention measures in PWIDs can reduce both prevalence and incidence of HCV infection [2,3,17]. These actions have focussed around injecting drugs as this was, and still remains the dominant route for HCV transmission in England.…”
Section: Discussionmentioning
confidence: 99%
“…Primary interventions aimed at reducing incident infections by the provision of sterile injecting equipment and reducing injection through opiate substitution therapy have had an impact on the prevalence of HCV in persons who inject drugs (PWIDs) [2,3,17]. In addition, treatment, which leads to viral clearance will clearly impact on both the burden of disease and onward transmission [11].…”
Section: Introductionmentioning
confidence: 99%
“…A modeling study about the structural determinants of the HIV epidemic among prostitutes in several countries showed that the decriminalization of sexual work would prevent from 33 to 46% new infections throughout a decade, which is higher to that found for the impact of the amplification of ART 96 . Another systematic review showed that harm reduction programs for drug users carried out in a structural scope (i.e., more access to syringes in drugstores and elimination of prohibitions REV BRAS EPIDEMIOL SEP 2015; 18 SUPPL 1: 43-62 of drug paraphernalia) are able to reduce the incidence of HIV and hepatitis C in the general population 99 . Even though structural interventions approach many actions and mobilize several fields of work, their most important impact comes from complementarity and synergy between the different types of intervention and involved parties, such as combined actions to change the macro and microstructural context, the delivery of services and health products and the mobilization of community 100 .…”
Section: Not All Methods Should Be Used In Sexual Relations: Structurmentioning
confidence: 99%
“…There are many reasons that criminological research may not translate into public policy interventions (Austin 2003;Schmitt 2013), but even when armed with relevant data, policymakers and legislators do not always make evidence-based choices (Lilienfeld et al 2013 although there is unimpeachable evidence that needle exchange programs are effective in reducing the spread of HIV and AIDS (Abdul-Quader et al 2013), programs of this kind are often opposed on moral and political grounds. Consequently, few such programs have been established in the United States (Lurie and Drucker 1997).…”
Section: The Politicization Of Federal Criminal Justicementioning
confidence: 99%